2007
DOI: 10.1093/chemse/bjm009
|View full text |Cite
|
Sign up to set email alerts
|

Component Information Is Preserved in Glomerular Responses to Binary Odor Mixtures in the Moth Spodoptera littoralis

Abstract: Natural odors are often complex mixtures of different compounds. These mixtures can be perceived to have qualities that are different from their components. Moreover, components can be difficult to distinguish within a blend, even if those components are identifiable when presented individually. Thus, odor components can interact along the olfactory pathway in a nonlinear fashion such that the mixture is not perceived simply as the sum of its components. Here we investigated odor-evoked changes in Ca2+ concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 55 publications
8
29
0
Order By: Relevance
“…This is in agreement with previous insect studies ( Deisig et al, 2006;Carlsson et al, 2007;Silbering and Galizia, 2007). However, at the output level, strong nonlinear interactions that could not be predicted from the single component patterns occurred in six of seven animals, even when controlling for concentration (see Materials and Methods, Optophysiology, Odor stimulation).…”
Section: Input/output Comparison Reveals Spatiotemporal Modulationsupporting
confidence: 92%
“…This is in agreement with previous insect studies ( Deisig et al, 2006;Carlsson et al, 2007;Silbering and Galizia, 2007). However, at the output level, strong nonlinear interactions that could not be predicted from the single component patterns occurred in six of seven animals, even when controlling for concentration (see Materials and Methods, Optophysiology, Odor stimulation).…”
Section: Input/output Comparison Reveals Spatiotemporal Modulationsupporting
confidence: 92%
“…Mixture interactions between general odours are known from other moth species (Carlsson et al, 2007;Namiki et al, 2008;Piñero et al, 2008), and we found consistent effects in male and female AL neurons to the mixture of pear ester and acetic acid, which has been shown to be behaviourally synergistic in both sexes (Landolt et al, 2007).…”
Section: Blend Interactionssupporting
confidence: 76%
“…Furthermore, olfactory information is significantly modulated by a dense network of local neurons in the first olfactory center of the insect brain, the antennal lobe (AL) (reviewed in Galizia and Rössler, 2010;Masse et al, 2009;Wilson, 2013;Wilson and Mainen, 2006). Nevertheless, physiological odor mixture responses in the AL are qualitatively predictable on the basis of mixture constituent responses in Drosophila (Olsen et al, 2010;Silbering and Galizia, 2007) and other insects (Carlsson et al, 2007;Deisig et al, 2006;Deisig et al, 2010;Fernandez et al, 2009;Joerges et al, 1997;Stierle et al, 2013; but see Anton and Hansson, 1996;Kuebler et al, 2011;Kuebler et al, 2012;Meyer and Galizia, 2012). Therefore, if single OSN class responses are already behaviorally meaningful, the innate hedonic valence of odor mixtures may in fact be predictable on the basis of the valences of mixture constituents.…”
Section: Introductionmentioning
confidence: 99%